Study of reading habits 1985 - Södermanland - Weibull, Lennart (University of Gothenburg, 1993)
This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of four municipalities in Södermanland: Eskilstuna, Flen, Strängnäs and Kungsör. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also a number of questions not asked in previous surveys. In this survey the respondents were asked about their opinion on the occurrence of incorrect or misleading information in various news media; if the news cover should be influenced by the editorial political standpoint; and the importance of a variety of different goals of society in the next ten years.

Denna undersökning ingår i forskningsprogrammet "Dagspresskollegiet". Målgruppen i denna undersökning var invånarna i fyra kommuner i Södermanland: Eskilstuna, Flen, Strängnäs och Kungsör. De flesta av frågorna är replikeringar av frågor som ställts i tidigare Läsvanestudier, det vill säga frågor om läsvanor, prenumerationer av papper, läsintressen och bakgrundsvariabler som kön, ålder, utbildning och festpreferenser. Det fanns också ett antal frågor som inte ställdes i tidigare undersökningar. I denna undersökning frågades respondenterna om deras åsikt om förekomsten av oriktig eller vilseledande information i olika nyhetsmedier; om nyhetsbrevet bör påverkas av den redaktionella politiska ståndpunkten; och vikten av en rad olika samhällsmål i de kommande tio åren.
Läsvanestudien 1985 - Södermanland
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap